Time-Trend Analyses of Bleeding and Mortality After Primary Percutaneous Coronary Intervention During Out of Working Hours Versus In-Working Hours: An Observational Study of 11 466 Patients. (June 2015) - Iqbal, M. Bilal; Khamis, Ramzi; Ilsley, Charles; Mikhail, Ghada; Crake, Tom; Firoozi, Sam; Kalra, Sundeep; Knight, Charles; Archbold, Andrew; Lim, Pitt; Mathur, Anthony; Meier, Pascal; et al.
Abstract : Background—: Primary percutaneous coronary intervention (PPCI) is the treatment of choice for ST-segment–elevation myocardial infarction. Resources are limited during out of working hours (OWH). Whether PPCI outside working hours is associated with worse outcomes and whether outcomes have improved over time are unknown. Methods and Results—: We analyzed 11 466 patients undergoing PPCI between 2004 and 2011 at all 8 tertiary cardiac centers in London, United Kingdom. We defined working hours as 9 AM to 5 PM (Monday to Friday). We analyzed in-hospital bleeding and all-cause mortality ⩽3 years, comparing OWH versus in-working hours. A total of 7494 patients (65.3%) were treated during OWH. Multivariable analyses demonstrated that PPCI during OWH was not a predictor for bleeding (odds ratio, 1.47; 95% confidence interval [CI], 0.97–2.24; P =0.071) or 3-year mortality (hazard ratio, 1.11; 95% CI, 0.94–1.32; P =0.20). This was confirmed in propensity-matched analyses. Time-stratified analyses demonstrated that PPCI during OWH was a predictor for bleeding (odds ratio, 2.00; 95% CI, 1.06–3.80; P =0.034) and 3-year mortality during 2005 to 2008 (hazard ratio, 1.23; 95% CI, 1.00–1.50; P =0.050), but this association was lost during 2009 to 2011. During 2005 to 2008, transradial access was predominantly used during in-working hours and PPCI during OWH was predictive of reduced transradial access use (odds ratio, 0.83; 95% CI, 0.71–0.98; P =0.033), but this association was lost during 2009 to 2011. Conclusions—: In this study of unselected patients with ST-segment–elevation myocardial infarction, PPCI during OWH versus in-working hours had comparable bleeding and mortality. Time-stratified analyses demonstrated a reduction in adjusted bleeding and mortality during OWH over time. This may reflect the improved service provision, but the increased adoption of transradial access during OWH may also be contributory. Abstract : Supplemental Digital Content is available in the text.